DIFERENSIASI PENDIDIKAN KARAKTER JAMAAH MASJID AL-IKHLAS DI LINGKUNGAN WISATA KARAOKE DUSUN SARIREJO SALATIGA 2019 - Riswanto, Muhammad (Fakultas Agama Islam UNDARIS, 2019)
Differentiation of character education for mosque worshipers Sarirejo is very varied regarding the strategies and curiculum education that is thaught. This study is aimed 1) to figure out the differentiation of character education for mosque worshipers al-ikhlas at the age of children, teenagers, and adults. 2) To find out the supporting and inhibiting factors of the differention of Al-ikhlas mosque character eductional at the age of children, adolescents and adults. The method appilied was descriptive qualitative research with a field research approach (field research). Qualitative data analysis was analytical inductive. This study found the differentiation of character education in Al-Ikhlas mosque. The differentiation of children's character education including: religiosity, honesty, discipline, curiosity, independence, caring for the environment, responsibility, loving to read, hard working and appreciating the achievement. The differentiation of teenager's character education such as: religiosity, discipline, curiosity, independence, caring for the environment, responsibility and social care. The differentiation of adult's character education including: religiosity, discipline, curiosity, independence, caring for the environment, responsibility, social care, tolerance. The supporting factors for the differentiation of children character education, teenagers and adult involving the existence of literature related to Islam. The existence of facilities such as benches, Quran, shalawat books, whiteboards, cleanliness of learning places, support from the parent's role, takmir and muslim community especially the government figures. The barrier factors of children's character education differentiation, teenager's differentiation and adult's differentiation were the backgrounds of various personality character of students, less conductive social environment and inadequate learning facilities.